Synthesis and Characterization of Schiff Base Complexes of Mn(II), Co(II) and Zn(II) - Parihari, R.K.; Patel, R.N. (Asian Journal of Chemistry, 2010)
In the present paper, we describe the synthesis and characterization of eight metal complexes of Mn2+, Co2+, and Zn2+ using schiff base ligand aalicylendene triethylenetetramine with some neutral ligands such as pyridine, quinoline, isoquinoline and γ-picoline.